2020
DOI: 10.3390/prosthesis2020008
|View full text |Cite
|
Sign up to set email alerts
|

Osseodensification Drilling vs. Standard Protocol of Implant Site Preparation: An In Vitro Study on Polyurethane Foam Sheets

Abstract: (1) Background: The aim of the present in vitro investigation was to evaluate, on polyurethane sheets, two different drilling techniques for dental implant positioning using osteocondensing burs compared to a standard type protocol. (2) Methods: Three different implant designs (Implacil De Bortoli UN III 4 × 10 mm, Restore RBM 4 (HEX) × 10 mm; Implacil De Bortoli UN II 4 × 10 mm) were evaluated (test implant (osteocondensing drills) and control implant (standard drills)). The insertion torque (IT), the removal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
(63 reference statements)
1
7
0
Order By: Relevance
“…The results of the present study showed that improved implant performance was found in higher polyurethane densities, as already reported in the literature, where a direct relationship between PS and bone density was found [4,7,11,[28][29][30][31]. Moreover, the polyurethane solid rigid blocks are able to avoid the local and anatomical variability of the native bone tissues, with no mechanical alteration connected with the environmental condition, and produce a standardized model for dental implant testing [20,23,26]. On the contrary, a limitation of the polyurethane substrates is that this material does not permit a validated evaluation of other parameters, such as the drilling temperature, or histological findings, and does not provide a consistent translational comparison of the implant interface with a human bone.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The results of the present study showed that improved implant performance was found in higher polyurethane densities, as already reported in the literature, where a direct relationship between PS and bone density was found [4,7,11,[28][29][30][31]. Moreover, the polyurethane solid rigid blocks are able to avoid the local and anatomical variability of the native bone tissues, with no mechanical alteration connected with the environmental condition, and produce a standardized model for dental implant testing [20,23,26]. On the contrary, a limitation of the polyurethane substrates is that this material does not permit a validated evaluation of other parameters, such as the drilling temperature, or histological findings, and does not provide a consistent translational comparison of the implant interface with a human bone.…”
Section: Discussionsupporting
confidence: 81%
“…The polyurethane solid rigid block has been proposed as an artificial substitute to simulate in vitro the mechanical behaviour of the bone tissue for dental implant positioning [18][19][20][21][22][23]. This material has the advantage of a homogeneous structure, and an additional dense layer can be added to simulate the cortical component of the native jawbone anatomy in the posterior maxilla [24][25][26]. The symmetrical linear chains of polyurethane monomers, provided by hexa-methylene sequences, results in an increased level of ordered and very strong superstructures, associated with the high magnitude of crystallinity of the polyurethane phase, and a large self-assembling process of linear hard components [27].…”
Section: Introductionmentioning
confidence: 99%
“…12 15 Comuzzi et al reported that, in standardized condition on low-density polyurethane study, the macro-geometry induced the main effect on the primary stability, while the osseodensification drilling procedure produced the more visible effect on stability in presence of a residual cortical bone. 16 Moreover, Gehrke et al reported the key role of the implant macro-geometry on a sheep study, while the self-tapping and round apex macro-geometry is able to influence significantly the percentage of new bone formation and the deposition of highly vascularized osteogenic matrix within the marrow spaces, 17 where the number and thickness of bone trabeculae increase with the loading of the dental implants. 18 In vivo, no radiographical and hystological evidence in crestal bone resorption were present were evident between the osseodensification procedure, 19 21 the drilling technique 22 and ultrasonic device approach.…”
Section: Introductionmentioning
confidence: 99%
“…The sample size measurement was oriented in accordance with the mean and standard deviation of a previous study, [28] while the alpha error was set at 0.05 with an effect size of 0.34, and the power (1-beta) was 0.95. The minimum number was 39 sites for each drilling protocol, with a total of 156 sites.…”
Section: Discussionmentioning
confidence: 99%